Comparison of capability and health-related quality of life instruments in capturing aspects of mental well-being in people with schizophrenia and depression. Issue 4 (27th July 2022) - Helter, Timea Mariann; Coast, Joanna; Łaszewska, Agata; Stamm, Tanja; Simon, Judit
Abstract : Background: There is increasing evidence that assessing outcomes in terms of capability provides information beyond that of health-related quality of life (HRQoL) for outcome evaluation in mental health research and clinical practice. Aims: To assess similarities and differences in the measurement properties of the ICECAP-A capability measure and Oxford Capabilities Questionnaire for Mental Health (OxCAP-MH) in people with schizophrenia experiencing depression, and compare these measurement properties with those of (a) the EuroQol EQ-5D-5L and EuroQol Visual Analogue Scale (EQ-VAS) and (b) mental health-specific (disease-specific) measures. Method: Using data for 100 patients from the UK, measurement properties were compared using correlation analyses, Bland–Altman plots and exploratory factor analysis. Responsiveness was assessed by defining groups who worsened, improved or remained unchanged, based on whether there was a clinically meaningful change in the instrument scores between baseline and 9-month follow-up assessments. Results: The two capability instruments had stronger convergent validity with each other (Spearman's rho = 0.677) than with the HRQoL (rho = 0.354–0.431) or the mental health-specific (rho = 0.481–0.718) instruments. The OxCAP-MH tended to have stronger correlations with mental health-specific instruments than the ICECAP-A, whereas the ICECAP-A had slightly stronger correlation with the EQ-VAS. Change scores on the capability instruments correlated weakly with change scores on the HRQoL scales (rho = 0.131–0.269), but moderately with those on mental health-specific instruments for the ICECAP-A (rho = 0.355–0.451) and moderately/strongly on the OxCAP-MH (rho = 0.437–0.557). Conclusions: Assessing outcomes in terms of capabilities for people with schizophrenia and depression provided more relevant, mental health-specific information than the EQ-5D-5L or the EQ-VAS. The ICECAP-A and the OxCAP-MH demonstrated similar psychometric properties, but the OxCAP-MH was more correlated with disease-specific instruments.